Potential impact on HIV incidence of higher HIV testing rates and earlier antiretroviral therapy initiation in MSM. (10th September 2015) - Phillips, Andrew N.; Cambiano, Valentina; Miners, Alec; Lampe, Fiona C.; Rodger, Alison; Nakagawa, Fumiyo; Brown, Alison; Gill, O. Noel; De Angelis, Daniela; Elford, Jonathan; Hart, Graham; Johnson, Anne M.; et al.
Abstract : Background: Increased rates of testing, with early antiretroviral therapy (ART) initiation, represent a key potential HIV-prevention approach. Currently, in MSM in the United Kingdom, it is estimated that 36% are diagnosed by 1 year from infection, and the ART initiation threshold is at CD4 + cell count 350/μl. We investigated what would be required to reduce HIV incidence in MSM to below 1 per 1000 person-years (i.e. <535 new infections per year) by 2030, and whether this is likely to be cost-effective. Methods: A dynamic, individual-based simulation model was calibrated to multiple data sources on HIV in MSM in the United Kingdom. Outcomes were projected according to future alternative HIV testing and ART initiation scenarios to 2030, considering also potential changes in levels of condomless sex. Results: For ART use to result in an incidence of close to 1/1000 person-years requires the proportion of all HIV-positive MSM with viral suppression to increase from below 60% currently to 90%, assuming no rise in levels of condomless sex. Substantial increases in HIV testing, such that over 90% of men are diagnosed within a year of infection, would increase the proportion of HIV-positive men with viral suppression to 80%, and it would be 90%, if ART is initiated at diagnosis. The scenarios required for such a policy to be cost-effective are presented. Conclusion: This analysis provides targets for the proportion of all HIV-positive MSM with viral suppression required to achieve substantial reductions in HIV incidence. Abstract : Supplemental Digital Content is available in the text